Performance of polysulfone/PANI membrane for humic acid separation - Ahmad, Azlinnorazi; Yunos, Muhamad Zaini; Harun, Zawati; Hassan, Mohd Fahrul; Adzila, Sharifah; Tajul Arifin, Ahmad Mubarak; Abdol Rahman, Mohd Nasrull; Abdul Haq, Reazul Haq; Baharulrazi, Norfhairna (The Italian Association of Chemical Engineering, 2017)
The effect of polymer mixed matrix membrane was investigated by mixing Polyaniline (PANI) in Polysulfone (PSf) membrane for humic acid separation. The purpose addition of PANI in PSf was to improve the membrane hydrophilicity and increase membrane permeability The membrane preparation was undergo phase inversion method at high concentration of PANI (0-15 wt.%). The characterization and performance of the membrane were evaluated in respect to membrane hydrophilicity, pure water flux and rejection properties against humic acid. The result showed that by blending PANI in PSf membrane, the contact angle decreased up to 17 %. This result indicate that addition of PANI improve surface hydrophilicity of membrane. Meanwhile, the addition of PANI increased membrane permeability up to 84 %. The rejection properties also improved up to 25 %. According to the membrane hydrophilicity and the performance against humic substance, PANI has a strong potential to be used as an additive in membrane fabrication.